Absorption, metabolism, and bioactivity of vitexin: recent advances in understanding the efficacy of an important nutraceutical. Issue 6 (15th February 2021) - Peng, Ye; Gan, Renyou; Li, Huabin; Yang, Mingxuan; McClements, David Julian; Gao, Ruichang; Sun, Quancai
Abstract: vitexin, an apigenin-8-C-glucoside, is widely present in numerous edible and medicinal plants. vitexin possesses a variety of bioactive properties, including antioxidation, anti-inflammation, anti-cancer, neuron-protection, and cardio-protection. Other beneficial health effects, such as fat reduction, glucose metabolism, and hepatoprotection, have also been reported in recent studies. This review briefly discusses the absorption and metabolism of vitexin, as well as its influence on gut microbiota. Recent advances in understanding the pharmacological and biological effects of vitexin are then reviewed. Improved knowledge of the absorption, metabolism, bioactivity, and molecular targets of vitexin is crucial for the better utilization of this emerging nutraceutical as a chemopreventive and chemotherapeutic agent.